Attempted Suicide: A Multilevel Examination of Inmate Characteristics and Prison Context: - Stoliker, Bryce E. (Criminal justice and behavior, 2018)
Correctional institutions in the United States witness higher rates of suicide compared with the general population, as well as a higher number of attempted suicides compared with completed cases. Prison research focused little attention on investigating the combined effects of inmate characteristics and prison context on suicide, with studies using only one level of analysis (prison or prisoner) and neglecting the nested nature of inmates in prisons. To extend this literature, multilevel modeling techniques were employed to investigate individual- and prison-contextual predictive patterns of attempted suicide using a nationally representative sample of 18,185 inmates in 326 prisons across the United States. Results revealed that several individual-level factors predicted odds for attempted suicide, such as inmate characteristics/demographics, prison experiences, having a serious mental illness, and symptoms of mental health issues. Some prison-contextual variables, as well as cross-level interaction effects, also significantly predicted odds for attempted suicide. Policy and research implications are discussed.